Prevalence of bovine tuberculosis in cattle of lower and middle ranges of north-western Himalayas - SHARMA, SUSHIL; PANDA, A K; KUMAR, ATUL; THAKUR, SIDHARATH DEV (The Indian Journal of Animal Sciences, 2019)
This study was conducted to ascertain the prevalence of bovine tuberculosis in cattle of different breeds reared under different faming systems and agro-climatic zones of Himachal Pradesh. Tuberculin reactors (17) were detected only in organized dairy farms. Prevalence (15/595, 2.5%) of the disease was highest in animals aged between 5-10 years with 88.2% (15/17) of total reactors being detected in this age group. Tuberculin reactors were found among animal from Red Sindhi crosses (11.8%, 13/110) and pure Jersey/HF animals (2.8%, 4/143). RT-PCR detected M. bovis in milk (20%, 2/10) and lymph node biopsy samples (17.6%, 3/17). M. bovis is zoonotic and shedding of bacteria in milk is a serious public health hazard. Raw milk and products prepared from unpasteurized or raw milk are major vehicles of M. bovis transmission and causation of extra pulmonary tuberculosis in humans.